Evolution Mechanism on Structural Characteristics of Lead-Contaminated Soil in the Solidification/Stabilization Process - Li, Jiang-shan (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
This book highlights the use of Solidification/Stabilization (S/S) to treat lead-contaminated soils, which are widely present in China. It reveals the evolutionary mechanism of the structural characteristics of Pb contaminated soil during the S/S process. In addition, the book systematically analyzes laws influencing the S/S process and its internal mechanisms, and develops new models for the strength prediction and Pb leaching prediction of S/S monolith. The results can provide essential theoretical guidance and parameter-related support for the design of Pb-contaminated soil S/S remediation and recycling solutions.